Epigenetic modifications of autophagy in cancer and cancer therapeutics. (November 2020) - Bhol, Chandra S.; Panigrahi, Debasna P.; Praharaj, Prakash P.; Mahapatra, Kewal K.; Patra, Srimanta; Mishra, Soumya R.; Behera, Bishnu P.; Bhutia, Sujit K.
Abstract: Epigenetic alterations, such as DNA methylation, histone modifications and miRNAs, have a significant role play in malignant cellular transformation and metastasis. On the other hand, autophagy has been reported to perform context-dependent roles in cancer; at times, it becomes lethal and abolishes tumorigenesis, whereas, at other instances, it protects cancer cells by providing a rescue mechanism under adverse conditions. Although epigenetics and autophagy are two important and independent cellular processes, various oncogenic and oncosuppressor proteins involve autophagy through epigenetic modifications and different signaling pathways, thereby regulating tumor growth and therapeutic response. Moreover, the importance of epigenetic modification of autophagy in cancer is reflected through its involvement in cancer stem cell maintenance, which in turn, contributes to tumor cell viability during dormancy leading to tumor recurrence. The effects of epigenetic modifications of autophagy in cancer is still ambiguous and less acknowledged; therefore, efforts have been made to understand its detail underlying mechanism to unveil new targets and avenues for better prognosis and diagnosis of cancer.